If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -7) + -1(y + 5) = 8y Reorder the terms: (-7 + y) + -1(y + 5) = 8y Remove parenthesis around (-7 + y) -7 + y + -1(y + 5) = 8y Reorder the terms: -7 + y + -1(5 + y) = 8y -7 + y + (5 * -1 + y * -1) = 8y -7 + y + (-5 + -1y) = 8y Reorder the terms: -7 + -5 + y + -1y = 8y Combine like terms: -7 + -5 = -12 -12 + y + -1y = 8y Combine like terms: y + -1y = 0 -12 + 0 = 8y -12 = 8y Solving -12 = 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -12 + -8y = 8y + -8y Combine like terms: 8y + -8y = 0 -12 + -8y = 0 Add '12' to each side of the equation. -12 + 12 + -8y = 0 + 12 Combine like terms: -12 + 12 = 0 0 + -8y = 0 + 12 -8y = 0 + 12 Combine like terms: 0 + 12 = 12 -8y = 12 Divide each side by '-8'. y = -1.5 Simplifying y = -1.5
| 4-30+5y=45 | | x^2=6.25 | | 2-x=5yz+4 | | x^6-2x^4+4x^2-8=0 | | 1+.8c=7 | | 8x+x=12+104 | | 24+6y=-12 | | 20=2x+12 | | 51pt-3p+4t= | | y=2*1 | | 1x^2-9x-6=0 | | (x^2+6x+5)-(x^2+4x-5)= | | 2y+4=6y | | 4y-4=6y-22 | | (6x)-(x+8)= | | -6=6/5b+5 | | 8(y+5)+y=3(y+3)+2 | | 25-5x-18-12x=0 | | y=1+5 | | 9x-19=2x+11 | | 6x-x=60+30 | | x^2-6x+153=0 | | 16a*2-14a+1a*2-3a= | | 25-5x-18-12x=10 | | x^2-6+153=0 | | 15x+6-(X+2)= | | 0.25(m+5)=-1.5 | | 12x=10x+60 | | 10y=-22 | | 1+6h=2+4h | | 14x-5=10x+7 | | 7y-14=21 |